RETRACTED ARTICLE: Assessment of aflatoxins in peanuts grown in the Pothohar area of Pakistan. Issue 3 (3rd July 2019) - Abbas, M.; Asi, M.R.; Anwar, F.; Mahmood, T.; Khan, A.M.; Yaqub, T.
Statement of Retraction: The following article has been retracted from publication in the Taylor & Francis journal, Food Additives & Contaminants: Part B: M. Abbas, M. R. Asi, F. Anwar, T. Mahmood, A. M. Khan and T. Yaqub, Assessment of aflatoxins in peanuts grown in the Pothohar area of Pakistan, Food Additives & Contaminants: Part B, http://www.tandfonline.com/doi/full/10.1080/19393210.2013.820221 . Version of record published online 26th July 2013. The Editor of Food Additives & Contaminants: Part B and Taylor & Francis note that the policy of the journal is to consider only original material, and authors are required to make a warranty to the effect that articles are not under consideration for publication by any other journal. The article was published in good faith. Subsequently, it has become known that a similar article was submitted to and published in World Academy of Science, Engineering and Technology, Volume 69 (2012). As this is contrary to our stated policy, the article is hereby retracted and should not be cited. It is Taylor & Francis policy that the Food Additives & Contaminants: Part B article be kept online, but also stating that the paper has been retracted, together with a link to this Retraction to ensure the integrity of the scientific record.